RESPONSES OF CYPRINUS CARPIO VAR . COMMUNIS TO CYHALO IN, A P E OID INSECTICIDE - Begum, A. Asia; Ramesh, M.; Noortheen, A.; Sampth, Hannah; Revathy, B. (Journal of Indian Fisheries Association, 2016)
Haematological and biochemical profiles in a freshwater teleost, Cyprinus carpio var. communis, exposed to sub-lethal toxicity of the insecticide cyhalothrin were studied. During the treatment, erythrocyte count, haemoglobin content and protein content decreased, whereas leucocyte count and glucose level increased. The data are discussed in relation to the significance of haematological and biochemical changes as non-specific biomarkers against anthropogenic stress. Keywords: Cyhalothrin, erythrocytes, leucocytes, haemoglobin, protein, glucose, Cyprinus carpio